Posisi Indonesia Pada Organisasi Internasional: Peran Strategis Dalam Pembentukan Hukum Internasional - Yustitianingtyas, Levina; Pratiwi, L.Ya Esty; Setyowati, Dewi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
International law functions as a foundation for relations between states and international organizations, and regulates various global issues such as human rights, peace and security. Indonesia, as the country with the fourth largest population and one of the main regional powers in Southeast Asia, plays a significant role in the development of international law. This legal writing focuses on the issue of the extent of Indonesia's contribution in participating in international organizations, and its role in drafting and implementing international legal norms. Indonesia has made many contributions to the international arena, namely in forming international agreements and global conventions, such as the UN Convention on the Law of the Sea (UNCLOS 1982) and the Kyoto Protocol. The legal writing method used is legal normative, with a conceptual approach and case approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The results of this legal writing provide an answer that Indonesia has also implemented international legal norms into its national law and Indonesia's position or role in various international activities has been taken into account. This shows that Indonesia not only functions as an active participant in international policy making, but also as a driver of significant change in advancing the principles of international law. This contribution not only strengthens Indonesia's position on the global stage but also helps shape a fairer and more inclusive international legal order.